Forest Cover Assessment in Tuv province of Mongolia Using MODIS and Landsat-7 ETM+ - Tsolmon, R; Yanagida, K; Erdenetuya, M; Ochirhuyag, L (Proceedings of the Mongolian Academy of Sciences, 2011)
The study aimed at determining the relative proportions of forest cover and other components in a mixed pixel. For this purpose a linear mixing model was used for the derivation of a land cover classification map in two study areas of Tuv province, Mongolia. Main types of forest cover change are forests to burn scars and agricultural fields in the study areas. In this paper, two reflective channels 3 and 4 of LANDSAT ETM+ and reflective channels land 2 of MODIS data was used to map five and four land components respectively. Clouds proportion was derived using MODIS data. A synergy between high-resolution MODIS and Landsat ETM+ data may greatly enhance the operational success of satellite based vegetation monitoring, in providing multi-spectral data on parameters of the environment. DOI: http://dx.doi.org/10.5564/pmas.v0i4.40 Proceedings of the Mongolian Academy of Sciences 2007 No 4 pp.50-59